A Conceptual Framework of Distributive Justice in Islamic Economics - Shafinah Begum Abdul Rahim (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
itical, behavioural and social sciences both in mainstream or Islam. Given its increasing relevance to the global village we share and the intensity of socio-economic problems invariably related to the distribution of resources amongst us, this work is aimed at adding value through a deeper understanding and appreciation of justice placed by the Syariah in all domains of of our economic lives. The existing works within this area appear to lean mostly towards redistributive mechanisms available in the revealed knowledge. Hence a comprehensive analysis of the notion of distributive justice from the theoretical level translated into practical terms is expected to contribute significantly to policymakers committed towards finding permanent solutions to economic problems especially in the Muslim world. It is a modest yet serious attempt to bridge the gap between distributive justice in letter and spirit as clearly ordained in the Holy Quran. The entire analysis is based on critical reviews and appraisals of the all relevant literary on distributive justice in Islamic Economics. The final product is a conceptual framework that can be used as a blueprint in establishing the notion of justice in the distribution of economic resources, i.e. income and wealth as aspired by the Syariah.